The repercussions of the double shocks on the Iraqi economy For the period (2014-2020) - Sabeeh, Zainab (The Gulf Economist, 2023)
The global economy is exposed to many shocks in terms of economic, social, health and security, the latest of which was the shock of the Corona pandemic and the accompanying decline in the level of economic activity as a result of the cessation of life wheel as well as the decline in oil prices as a result of low global demand for oil, which led to an increase in oil supply. This shock, which swept all economies of the world, was negatively reflected negatively on oil countries. As Iraq is a rentier country dependent on oil rents in an almost complete way, it is affected by any emergency fluctuations in the oil market. The Iraqi economy witnessed two double shocks, the first of which was the shock in 2014, the occupation of most of the country, which was accompanied by a decrease in oil prices. The second is a shock in 2020, represented by the Corona pandemic and the decline in oil prices. The two shocks have an impact on all joints of the Iraqi economy